More than skin deep - Gaynes, David; Out of the Box (Firm) ([Boston, MA : Fanlight Productions, 2001)
This video examines issues of self-esteem and aging, through the stories and insight of six nursing home residents. It takes an evocate look at the connections between living well, aging with dignity, and looking good
Title from title screen
DVD format
Keywords: Older people -- Nursing home care; Older people -- Nursing home care -- Psychological aspects; Nursing home patients